The KDEL receptor - Bräuer, P (2019)
The integrity of the eukaryotic secretory pathway is maintained through selective export and retrieval of proteins between the endoplasmic reticulum (ER) and Golgi. An essential component of ER protein retrieval is the KDEL receptor (KDELR), an integral membrane protein that recognises a C-terminal KDEL signal sequence (a C-terminal KDEL peptide in mammals and HDEL in plants and Saccharomyces cerevisiae) in a pH-dependent process. However, the evolutionary origin of the KDELR, the mechanism through which it binds and releases cargo, and how it interacts with cellular trafficking machinery, has remained elusive. This thesis presents high resolution crystal structures of the Gallus gallus KDELR 2, in several states: one apo structure, three peptide-bound structures, and one structure of the KDELR bound to an antagonistic synthetic nanobody (Sybody). These structures are compared and analysed to answer questions about the KDELR’s mechanism of action and likely origin of the KDELR. In vivo cell localisation and in vitro binding assays were developed to examine different mutants of the KDELR and test hypotheses generated from structural data. Synthesising the data, a model for the retrieval of ER resident proteins from the Golgi, by the KDELR, was developed. The model involves pH sensitive binding to cargo proteins, controlled by the protonation state of a key histidine residue which stabilises a hydrogen bond within the receptor. The stability of this hydrogen bond in the bound-state locks the receptor onto its cargo until the pH changes. The specificity of the KDELR for HDEL or KDEL motifs was also explored, and appears to depend on differential interactions of the HDEL and KDEL signals with a tryptophan residue in the binding pocket. Comparison with other membrane proteins suggests how the KDELR likely evolved from an ancestral secondary active transporter, demonstrating that transporter-like architectures may have been adapted to transmit signals across cell membranes.